Identifying reasons for non-acceptance of influenza vaccine in healthcare workers: an observational study using declination form data - Aimee Challenger; Petroc Sumner; Eryl Powell; Lewis Bott (BMC, 2023)
Abstract Background Healthcare workers are sometimes required to complete a declination form if they choose not to accept the influenza vaccine. We analysed the declination data with the goal of identifying barriers to vaccination uptake across seasons, staff groups, and pre- and post- arrival of COVID-19. Methods Reasons for declining the vaccine were gathered from N = 2230 declination forms, collected over four influenza seasons, 2017/2018, 2018/2019, 2019/2020 and 2020/2021, from a single health board in the UK. Reasons were classified according to ten categories and the resulting distribution analysed across year and staff groups. A further analysis considered the two most prevalent categories in more detail. Results Fear of adverse reactions and Lack of perception of own risk were identified as primary reasons for not accepting the vaccine across time and across staff groups. However, there was no evidence that Lack of concern with influenza, or Doubts about vaccine efficacy was prevalent, contrary to previous findings. Overall, reasons fitted a pattern of underestimating risk associated with influenza and overestimating risk of minor adverse reactions. There were also differences across years, χ2(24) = 123, p < .001. In particular, there were relatively fewer Lack of perception of own risk responses post-COVID-19 arrival than before, χ2(8) = 28.93, p = .002. Conclusion This study shows that data collected from declination forms yields sensible information concerning vaccine non-acceptance without the difficulties of retrospective or pre-emptive reasoning suffered by questionnaires. Our findings will aid messaging campaigns designed to encourage uptake of the influenza vaccine in healthcare workers. In particular, we argue for an approach focused on risk perception rather than correction of straightforward misconceptions.